Nonpharmacological management of persistent pain in elite athletes: Rationale and recommendations - Moseley, G. L.; Baranoff, J.; Rio, E.; Stewart, M.; Derman, W.; Hainline, B. (Clinical Journal of Sport Medicine, 2018)
Persistent pain is common in elite athletes. The current review arose from a consensus initiative by the International Olympic Committee to advance the development of a standardized, scientific, and evidence-informed approach to management. We suggest that optimal management of persistent pain in elite athletes requires an understanding of contemporary pain science, including the rationale behind and implementation of a biopsychosocial approach to care. We argue that athletes and clinicians need to understand the biopsychosocial model because it applies to both pain and the impact of pain with special reference to the sport setting. Management relies on thorough and precise assessment that considers contributing factors across nociceptive, inflammatory, neuropathic, and centrally acting domains; these can include contextual and psychosocial factors. Pain management seeks to remove contributing factors wherever possible through targeted education; adjustment of mechanical loading, training, and performance schedules; psychological therapies; and management of inflammation.